Eine Neuformulierung der Quantitätstheorie des Geldes - Karl Brunner (Kredit und Kapital, 1970)
A Reformulation of the Quantity Theory of Money The point of departure is the incapacity of traditional price theory to explain the wıdespread nonutilization of agents of production as encountered in the mass unemployment of the thirties. Keynes attempted to overcome this difficulty with a theory of interest in which the movements of interest rates appeared as the mirror image of a mechanism of relative prices. Then, in the Keynesian theory of the forties, this price theory approach was dropped and a so-called transfer mechanism was interpreted with the help of credit costs and entrepreneurial reaction to changes in them. The ensuing econometric investigations, however, brought an abundance of contradictory results on the significance of the interest mechanism. Hence the question can now be raised of whether the prevailing theoretical model should not be given up altogether, and an attempt made to reformulate price theory in a form which gives renewed valıdity both to the original programme of Keynes and that of Irving Fisher. Essentially this reformulation necessitates two extensions: On the one hand, the reactions to market stimuli must be generalized so that capital assets and liabilities, and also their returns and costs can be included. On the other hand, neither information nor changes in the structure of resource utilization are produced without marginal costs (or average costs). The article ventilates these two lines of approach thoroughly and develops from them a comprehensive price theory which also includes monetary phenomena. The object is a reformulation of the Quantity Theory in which the mechanism of relative prices plays a central role for capital assets, liabilities and output.
Keywords: 330